Critical Intercultural Pedagogical Experiences: The case of two public schools - Oviedo-Gómez, Hans; Jaramillo-Cárdenas, Catalina (Colombian Applied Linguistics Journal, 2024)
This article is the result of our research interest in the concept of Critical Interculturality (CI) along with our professional pedagogical experiences at the public-school level. The experiences took place in two different regions in Colombia, Medellín, Antioquia, and Florencia, Caquetá. These experiences were initially systematized in a PhD seminar concerning Critical Intercultural theories. First of all, we conceptualise CI from a Latin-American perspective associated with patterns of power and hierarchical structures, while bringing to light other ways of being, living, and knowing. Then, we look at the current stage of English Language Teaching (ELT) Colombian scholarship on CI, which is increasingly being studied from the standpoint of theory rather than practice. Finally, we describe two experiences that highlight public school teachers’ practices from a critical intercultural view going beyond CI theory by categorising and proving that it is possible to undertake authentic critical intercultural pedagogical experiences in the EFL/ELT field.